Vibration and Airblast Standards for Underwater Blasting in Virginia - David K. Miller; Bill Yancey; Gordon Matheson (International Society of Explosives Engineers, 1999)
"Current regulatory limits for blast vibration and airblast control in Virginia do not specifically addressunderwater explosive testing. Underwater detonation of explosives generates an initial shock wave and a gas bubble. The gas bubble expands and collapses several times before reaching the water surface. This expansion and collapse of the gas bubble as it rises to the surface is called a “bubble pulse”. The bubble pulse generates low frequency vibrations that have the most potential for damaging structures and causing blasting complaints even below damage levels."